A study on estimation the trend towards financial statement analysis of Employees Provident Fund / Siti Noor Ain Mohd Rapeai - Mohd Rapeai, Siti Noor Ain (2011)
This study is conducted to estimate the financial performance of Employees Provident Fund (EPF). Financial statement analysis is an evaluative method of determining the past, current and projected performance of a company. Other words, financial statement is very important to the company to them analyze the performance and to know the potential of the company. This study analyze EPF financial statement from the year 2005 until 2009 by using comparative analysis which is index number trend analysis, common size analysis method and finally, financial ratio analysis. Beside, this study would like to identify either the company was in good condition during the global economic crisis on 2008 and also the trend facing by the company itself either uptrend or downtrend. For completion of this study, the secondary data it’s really helping to get the information. The data is taken from the external sources such as the annual report of EPF start from 2005 until 2009, the article and journal and also from the internet.